1979
DOI: 10.1515/znc-1979-3-404
|View full text |Cite
|
Sign up to set email alerts
|

New C30-Carotenoic Acid Glucosyl Esters from Pseudomonas rhodos

Abstract: The carotenoid pigments of the Gram-negative bacterium Pseudomonas rhodos were identified as 4,4′-diapocarotene-4-oic acid, di (β,ᴅ-glucosyl) 4,4′-diaptocarotene-4,4′-dioate, and β,ᴅ-glucosyl-4,4′-diapocarotene-4-oate-4′-oic acid. One hydroxy group of the glucose moieties, probably at C (6), was esterified with one of several fatty acids (12:0, 14:0, 14:1, 16:0, 1 6 :1).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
0
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 0 publications
3
28
0
1
Order By: Relevance
“…2). These results confirmed the aglycon of 4 to be diapolycopenedioic acid [12]. The UV-VIS spectrum of 1 was closely similar to that of diapolycopenedioic acid.…”
Section: Structural Elucidationsupporting
confidence: 77%
See 2 more Smart Citations
“…2). These results confirmed the aglycon of 4 to be diapolycopenedioic acid [12]. The UV-VIS spectrum of 1 was closely similar to that of diapolycopenedioic acid.…”
Section: Structural Elucidationsupporting
confidence: 77%
“…Diapolycopenedioic acid glucosyl ester [12] from Methylobacterium rhodinum ATCC 14821 (formerly Pseudomonas rhodos) has been reported previously as a compound related to diapolycopenedioic acid xylosyl esters. The aglycons of the compounds identified in this study were identical, while the diapolycopenedioic acid glucosyl ester possessed a b -glucose ester at C-4 of diapolycopenedioic acid.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…agreement with those of 4,4 -diapolycopene-4,4 -dioic acid dimethyl ester, which were partially reported in the previous report 8 . The 13 C NMR, 1 H-1 H DQF COSY, HMQC and HMBC analyses of 2 also confirmed that 2 was 4,4 -diapolycopene-4,4 -dioic acid dimethyl ester.…”
Section: Structural Elucidationsupporting
confidence: 92%
“…Different types and levels of modification of this C 40 backbone account for the majority of known carotenoids. C 30 carotenoid pathways starting with the condensation of two molecules of farnesyl diphosphate (C 15 PP) to form (15Z)-4,4Ј-diapophytoene (also called dehy-drosqualene) are much less widespread, having been found only in a small number of bacteria such as Staphylococcus, Streptococcus, Heliobacterium, and Methylobacterium species (55,100,101,129,130,198,205,206). These initial C 30 and C 40 condensation products are dehydrogenated in a stepwise manner by desaturase enzymes, which represent the next important branch points for pathway diversification (70).…”
Section: Overview Of Carotenoid Biosynthetic Pathwaysmentioning
confidence: 99%